Adaptation of Web 2.0 Applications in State Agricultural University Websites under Indian Council of Agricultural Research (ICAR) - A Content Analysis - C K, Kiran; P V, Vijesh; M K, Joseph (Qualitative and Quantitative Methods in Libraries, 2022)
The study focuses on the adaptation of Web 2.0 applications in State Agricultural University Websites. The data was collected by website observation and content analysis. This study scrutinized the availability and accessibility of Web 2.0 in Agricultural University websites under ICAR. The study identified that among the 63 State Agricultural University websites, 62 of them have their website. There are 12 different Web 2.0 applications identified in Agricultural University websites. Facebook (53.96%), Twitter (44.44%), YouTube (41.26%), and Instagram (12.69%) are the major Web 2.0 Applications used in Agricultural University websites. The findings of the study discussed the accuracy of links available on the websites.